"Part of being human": evaluating the 4Ps model to support inpatient staff teams in reflecting on interpersonal dynamics. Issue 4 (11th July 2019) - Jones, Lindsay; Annesley, Phyllis
Abstract : Purpose: An innovative training approach was developed to enable staff working with complex cases, including personality disorder, to reflect on and work with the interpersonal dynamics of their interactions with service users. The aim of this approach is to support effective, compassionate and boundaried care. An overview of the model and development of the training is provided along with presentation and discussion of outcome data. Implications for future practice are also considered. Design/methodology/approach: One-day workshops were provided within inpatient forensic women's services. Nine workshops were delivered with 96 multidisciplinary staff having attended in total. Evaluation tools were developed to ascertain participants' feedback regarding the training including its relevance and potential for impact on practice. Feedback was analysed using a mixture of quantitative and qualitative methods. Findings: The evaluation demonstrated that the training was well received by a motivated group of participants and was felt to be relevant to their clinical practice. Research limitations/implications: The evaluation is limited by the lack of a follow-up to assess the longer-term impacts of the training and whether the positive effects of the training were maintained. Practical implications: The findings demonstrate that the training can be delivered within a short time frame, which makes the training efficient and cost effective. Social implications: The training can develop practitioners' skills in delivering compassionate and boundaried care in line with key NHS drivers for staff working with complex service users. Originality/value: The 4Ps model enables staff with little or no psychotherapy training to deliver psychologically informed care which takes account of interpersonal dynamics and positively contributes to relational security, with an emphasis on reflecting on self and others.